One-stage surgery by a halo-vest to treat simultaneous double spine fractures–dislocation in a patient with ankylosing spondylitis: case report and review of literature - Wang, Liang; Qiu, Youcai; Wang, Can; Liu, Tielong; Lu, Xuhua (Frontiers in Surgery, 2024)
Background: In this study, we report the outcome of one-stage surgery by halo-vest to treat simultaneous double spine fractures-dislocation in patient with ankylosing spondylitis (AS).We report a 57-year-old man with AS who sustained simultaneous double spine fractures due to a traffic accident. We performed open approach after successful closed reduction by halo-vest. At the one-year follow-up, we finally achieved bone union after postoperative. At the 3-year follow-up visit, he reported a significant resolution of both cervical and back pain and had returned to his routine daily activities.This is the first report of halo-vest to treat simultaneous double spine fractures-dislocation in patient with AS. The authors include five research studies that situates this case study in the existing literature and highlights a gap in current knowledge. Based on our experience with this case and a review of the literature, one-stage surgery by halo-vest is an effective option for simultaneous double spine fractures-dislocation in patient with AS.